2022
DOI: 10.35445/alishlah.v14i4.2488
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Hand Puppets from Used Socks and Let's Read Application as Learning Media to Improve Students’ Story-Telling Skills

Abstract: This research aims at describing the utilization of hand puppets made from used socks adn Let’s Read Application as a storytelling medium in improving the speaking skills of the students at Faculty of Teacher Training and Education (FKIP) Al Washliyah Univeristy (Univa), Medan. This study also aims to 1) produce the benefits of hand puppets from used socks and the Let's Read application as learning media, 2) test the feasibility of the learning media, and 3) test the effectiveness of the media. This study uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…One of the successes of learning is determined by a support system in the form of a syllabus, learning models, learning media, and appropriate learning resources (Sya'bandari et al, 2022). To apply the values of Al-Washliyah figures to students, a learning program is needed to integrate these values, for example, through learning media, models, methods, and teaching materials (Siregar et al, 2022). The VCT learning model is the right alternative to integrate and distribute the values of Al-Washliyah figures to students so that they are able to apply these values in their daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…One of the successes of learning is determined by a support system in the form of a syllabus, learning models, learning media, and appropriate learning resources (Sya'bandari et al, 2022). To apply the values of Al-Washliyah figures to students, a learning program is needed to integrate these values, for example, through learning media, models, methods, and teaching materials (Siregar et al, 2022). The VCT learning model is the right alternative to integrate and distribute the values of Al-Washliyah figures to students so that they are able to apply these values in their daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…Since the data are words, a research uses qualitative method. As stated by Moleong in Siregar, Nasution & Pardi (2022), gualitative method is as a research strategy to produce descriptive data and the research results are in the form of written or spoken words from people and observed behavior. The location of this research in Khairul Imam Integrated Islamic Kindergarten (TK Khairul Imam) located on Jala STM/Suka Teguh No.…”
Section: Methodsmentioning
confidence: 99%
“…The development of increasingly sophisticated technology has become an important means to achieve educational goals that are more effective and efficient (Siregar, Nasution & Pardi, 2022). So, language as a medium of communication becomes very important especially English as one of international languages.…”
Section: Introductionmentioning
confidence: 99%
“…Learning media can be interpreted as a tool that educators can use to support the process of delivering information to students (Rusmardiana et al, 2022). Furthermore, Siregar et al (2022) explain that the use of instructional media is important to develop the skills of educators and students in carrying out the teaching and learning process. Therefore, the use of learning media supports the achievement of learning objectives namely the achievement of indicators of storytelling skill which includes articulation, fluency, and pronunciation (Syatriana et al, 2022).…”
Section: Introductionmentioning
confidence: 99%